CEREBRAL CIRCULATION AND COGNITION IN PATIENTS WITH CORONARY HEART DISEASE UNDERWENT CORONARY BYPASS OPERATION - М. М. Petrova; S. V. Prokopenko; О. V. Eremina; Е. Yu. Mozheyko; D. S. Kaskaeva; М. I. Gankin (Российский кардиологический журнал)
Aim. To assess the  condition  of cerebral  circulation and  cognitive functions  in patients  with coronary  heart  disease (CHD), underwent  coronary  bypass  (CBG) operation  under on-pump  conditions and to evaluate the influence of citicoline on the higher brain functions at earlier and delayed periods post-surgery.Material and methods. In the Federal center  of cardiosurgery  (Krasnoyarsk city) 66 patients studied, with diagnosis CHD. Patients selected to 2 groups. Main group (n=36) as  a medium  for cerebral  neuroprotection we used  citicoline (Ceraxon): intravenous, 1 day before surgery, 1000 mg on 200 mL of saline, and then for 7 days after  surgery,  with further  intake  of  the  drug  900  mg/daily  for  2  months.  In comparison  group (n=30) there was no neuroprotection in peri-operation period. Results. By the 12th month after surgery, cognition returned  to baseline values. In controls,  by 12 months after CBG, cognition returned  to baseline  only by the test “visual memory” of 5 words (direct remembering).Conclusion. Neuroprotection by citicoline might be a method  for improvement of cognition  in patients  after  such  damaging  events  as  on-pump  operation,   and therefore make it to reach higher level of daily functioning of post-CBG patients.